2014
DOI: 10.1109/tps.2013.2297173
|View full text |Cite
|
Sign up to set email alerts
|

Review on the History, Research, and Applications of Electrohydrodynamics

Abstract: Corona discharge refers to the phenomenon when the electric field near a conductor is strong enough to ionize the dielectric surrounding it but not strong enough to cause an electrical breakdown or arcing between conductors or other components. This phenomenon is unwanted and dangerous in high-voltage systems; however, a controlled corona discharge may be used to ionize a fluid and induce motion by directly converting the electrical energy into kinetic energy. Phenomena that involve the direct conversion of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
61
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(62 citation statements)
references
References 142 publications
0
61
0
1
Order By: Relevance
“…Among other emerging air cooling technologies proposed as alternatives to rotary fans such synthetic jets and piezoelectric fans, electrohydrodynamic (EHD) air movers have great potential to overcome the limitations of miniaturized rotary fans in modern microelectronic applications [1]. A recent comprehensive review study on the EHD phenomenon and its applications concluded that EHD air pumps can be used ideally as cooling solutions in confined spaces, on-chip and small-scale microelectronics due to their unique feature of having a wide range of flexibility and scaling ability [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among other emerging air cooling technologies proposed as alternatives to rotary fans such synthetic jets and piezoelectric fans, electrohydrodynamic (EHD) air movers have great potential to overcome the limitations of miniaturized rotary fans in modern microelectronic applications [1]. A recent comprehensive review study on the EHD phenomenon and its applications concluded that EHD air pumps can be used ideally as cooling solutions in confined spaces, on-chip and small-scale microelectronics due to their unique feature of having a wide range of flexibility and scaling ability [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been increased interest in incorporating electrohydrodynamic flows (often called ionic winds) into portable electronics devices to introduce forced convective cooling (Allen and Karayiannis, 1995;Fylladitakis et al, 2014). Ionic winds have several advantages over mechanical fans; in particular they can be easily miniaturized (Hsu et al, 2007;Tirumala et al, 2011), have no moving parts, and produce small acoustic signals.…”
Section: Introductionmentioning
confidence: 99%
“…Corona electrodes (wires) at high voltages create corona processes that ionize nearby air molecules, propelling the air molecules towards adjacently located grounded collecting electrodes (rods) [6,7,14,15]. The EFA does not greatly hinder the free air stream because its minimal configuration consists of only thin electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The EFA does not greatly hinder the free air stream because its minimal configuration consists of only thin electrodes. Corona electrodes (wires) at high voltages create corona processes that ionize nearby air molecules, propelling the air molecules towards adjacently located grounded collecting electrodes (rods) [6,7,14,15]. Bulk air movement (airflow) is produced when the charged molecules travel towards the collecting electrode, transferring both their charges and momentum to the neutral molecules they collide with along their path.…”
Section: Introductionmentioning
confidence: 99%